2016
DOI: 10.1016/j.intermet.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ti content on the microstructure and mechanical behavior of (Fe36Ni18Mn33Al13)100−xTix high entropy alloys

Abstract: a b s t r a c tThe microstructure and mechanical properties studies of a series of two-phase f.c.c./B2 (ordered b.c.c.) lamellar-structured, high entropy alloys (HEA) Fe 36 Ni 18 Mn 33 Al 13 Ti x with x up to 6 at. % Ti have been investigated. X-ray microanalysis in a TEM showed that the Ti resided mostly in the B2 phase. The lamellar spacing decreased significantly with increasing Ti content from 1.56 mm for the undoped alloy to 155 nm with an addition of 4 at. % Ti, leading to a sharp increase in room-temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…3 c and d indicates that the B2 phase is enriched in Ni and Al, while the f.c.c. matrix phase is enriched in Fe, Mn and Cr, which is consistent with the phase equilibria observed in other f.c.c./B2 two-phaseFeNiMnAl alloys[27,28].A BF TEM image of carbides in the 1.1 at. % C-doped HEA cold rolled and annealed at 1273 K for 1 h is shown inFig.…”
supporting
confidence: 85%
“…3 c and d indicates that the B2 phase is enriched in Ni and Al, while the f.c.c. matrix phase is enriched in Fe, Mn and Cr, which is consistent with the phase equilibria observed in other f.c.c./B2 two-phaseFeNiMnAl alloys[27,28].A BF TEM image of carbides in the 1.1 at. % C-doped HEA cold rolled and annealed at 1273 K for 1 h is shown inFig.…”
supporting
confidence: 85%
“…Contrasting the EDX results of the sample without Ti to that containing 3.0 wt.% Ti, some significant differences were observed. Figures 6 and 7 show the maps of the Here, the elemental mapping further confirms the possibility of the presence of all the elements in the solid solutions as previously reported [14,15] and that the lamellar structure diminishes with increasing Ti content. Moreover, coarse grains with some Ti precipitates on the grain boundaries formed with addition of 3.0% Ti.…”
Section: Effect Of Ti On the Microstructure Of Fe 31 Mn 28 Ni 15 Al 2supporting
confidence: 82%
“…From this figure, it can be observed that addition of Ti up to 3.0 wt.% increased significantly the hardness of the alloy from ∼310 to 500 (Hv). According to the explanation of the reported works [14][15][16], the strength of the current alloys are expected to improve because of both solid solution strengthening by Ti addition and by the decrease in the lamellar spacing following the Hall-Petch relationship [19]. Increasing the cooling rate by decreasing the section size down to 5 mm showed little improvement in the hardness.…”
Section: Mechanical Properties Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several works have been performed so far to obtain a comprehensive understanding of the effect of constitutive elements on the microstructure, phase composition and mechanical properties of HEA [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Nitride coatings from HEA have received particular attention because of improved physical and mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%